Pengaruh Penambahan Phasa Change Material (PCM) Terhadap Sistem Penyimpanan Energi Termal Baterai Pasir - YARDESH AOETPAH; Matheus M. Dwinanto; Verdy A. Koehuan; Rima N. Selan (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2025)
The thermal energy storage system through sand media is one of the energy storage solutions that has great potential to be developed to meet energy needs. PCM is a type of latent heat storage that has been developed as a good thermal energy storage material. The purpose of this study was to analyze the efficiency of thermal energy storage in sand media equipped with phase change material (PCM) stored in a drum container as a sand battery. The results of this study indicate that the use of sand batteries without PCM tends to be low at the beginning of the heating time by the heater element and increases at the end of the heating time. The use of PCM where the PCM changes phase from solid to liquid tends to absorb higher heat than media without PCM so that efficiency increases and tends to be stable until the heat release process is also longer than media without PCM. While in media without PCM, there tends to be a slower increase in thermal efficiency and a shorter time for the heat release process than media with